Genetic diversity and population structure of cowpea mutant collection using SSR and ISSR molecular markers - Sara Diallo; François Abaye Badiane; Badji-N’Poneh Ange Kabkia; Issa Diédhiou; Made Diouf; Diaga Diouf (Scientific Reports)
Abstract Cowpea is a seed legume, important for food and nutritional security in Africa’s arid and semi-arid zones. Despite its importance, cowpea is experiencing a loss of genetic diversity due to climate change. Therefore, this study aimed to evaluate the genetic variability of 33 cowpea mutant collections using 20 SSR and 13 ISSR markers. This analysis shows an average number of alleles of 5.15 for SSR and 6.7 for ISSR. The highest average genetic distance based on Nei’s index among subgroups was 0.740 and the value of polymorphism information content varied from 0.02 to 0.23 for SSR and from 0.05 to 0.36 for ISSR. Our results revealed high genetic diversity based on the GD (0.126), Fst (0.513), and Shannon information index (0.246). The population structure analysis showed 3 and 4 clusters for ISSR and SSR markers, respectively. Genetic variation, as assessed by analysis of molecular variance, mostly indicates higher genetic diversity within the population than among populations. The hierarchical clustering of combined SSR and ISSR markers grouped the accessions into four groups, supporting the STRUCTURE analysis results. Additionally, the combination of SSR and ISSR provided better information on the level of genetic diversity, and population structure, and was more effective in determining the relationship between cowpea collection. This study enhances our understanding of the genetic organization of our mutant collection which can be used in breeding programs in the era of climate change.